2019
DOI: 10.3390/ijerph16162971
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Suicide in Mexico City: A Time Series Analysis, 2000–2016

Abstract: The association between air pollution and suicide has recently been under examination, and the findings continue to be contradictory. In order to contribute evidence to this still unresolved question, the objective of the present study was to evaluate the association between air quality and daily suicides registered in Mexico City (MC) between 2000 and 2016. Air quality was measured based on exposure to particulate matter under 2.5 and 10 micrometers (µm) (PM2.5 and PM10, respectively), ozone (O3), nitrogen di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…Many researches have explored the health effects of air pollution with time-series methods (Astudillo-García et al 2019 ; Guo et al 2017 ; Katsouyanni et al 1995 ; Luo et al 2020 ; Mokoena et al 2019 ), but few studies specifically measured the association between ambient air pollution and COPD mortality. Evidence on the short-term effects of ambient air pollution on COPD mortality is still not conclusive to date.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have explored the health effects of air pollution with time-series methods (Astudillo-García et al 2019 ; Guo et al 2017 ; Katsouyanni et al 1995 ; Luo et al 2020 ; Mokoena et al 2019 ), but few studies specifically measured the association between ambient air pollution and COPD mortality. Evidence on the short-term effects of ambient air pollution on COPD mortality is still not conclusive to date.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies in South Korea have identified deleterious effects of both short- and long-term exposure to air pollutants on suicide [ 15 , 16 , 29 , 30 ]. However, recent results from Mexico City showed no evidence of an association between short-term air pollution exposure and daily suicides [ 31 ]. Similarly, a time series analysis showed no statistically significant associations between air pollution and suicide in four Colombian cities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other recent evidence has emphasized the importance of comorbidities in the association between air pollution and suicide [ 15 , 16 , 31 ]. In 2010, Kim et al showed that suicide risk from increased PM 10 exposure was particularly intensified among participants with preexisting cardiovascular disease, although no significant association was found between short-term PM 10 exposure and suicide in cancer patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researches have explored the health effects of air pollution with time-series methods [13][14][15][16][17], but few studies speci c measured the association between ambient air pollution and COPD mortality. Furthermore, the characteristics of air pollution in different regions vary substantially.…”
Section: Introductionmentioning
confidence: 99%